Pola Hubungan Guru, Siswa, dan Orang Tua pada Model Wali Kelas Tetap di SD Aisyiyah Unggulan Gemolong - Wulandari Wulandari; Almuntaqo Zainuddin (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The fixed or looping homeroom model shows the potential to improve the relationship between teachers, students, and parents. This research was conducted to find out and describe the model of the permanent homeroom teacher and its impact on the relationship between teachers, students, and parents at SD Aisyiyah Unggulan Gemolong using a qualitative descriptive approach and a phenomenological model. The techniques used in the research are observation, interviews, and documentation. The results of the study show that the homeroom model at SD Aisyiyah has a positive impact. The existence of this system allows homeroom teachers to improve the quality of learning and create a comfortable, open, and supportive environment for learning and development. Good proximity between homeroom teachers, students, and parents has a significant influence on students' academic success and emotional development. This model also generates a sense of trust, comfort, and closeness that makes students feel more comfortable in learning and interacting at school. This model of a permanent homeroom teacher is effective and useful in education at SD Aisyiyah and has received positive support from students' parents. Overall, the homeroom model at SD Aisyiyah has succeeded in building a good relationship between homeroom teachers, students, and parents, which consistently and continuously supports the academic and social development of children at the school.